Historia zatrzymana w kalendarzu - Stobiecki, Rafał (Zeszyty Wiejskie, 2016)
This paper is an attempt to reflect on the calendar as a historical source for contemporary history. The author’s commentary was prompted by Kalendarz robotniczy na rok 1953 (Workers’ calendar for 1953) published by “Książka i Wiedza”. The publication came out at the height of Stalinism; analyzing it allows one to take a closer look at the atmosphere of this period from its own unique perspective, as well as search for its characteristics. The aim of this paper boils down to two questions. What sort of vision of the world, and of humanity emerges from the calendar? What role was played by historical content, or speaking more broadly, what views about the past, as in historical memory, were supposed to be imposed, popularized, and disseminated by the aforementioned publication?